Sex and The city of ladies : rewriting history with Cleopatra, Lucrezia Borgia and Catherine the Great /: rewriting history with Cleopatra, Lucrezia Borgia and Catherine the Great. (2020) - Hilton, Lisa, 1974-
No abstract available